THE CORRELATION OF KNOWLEDGE AND ATTITUDE WITH GIVING COLOSTRUM TO NEWBORN IN PUSKESMAS TAPING HILIR II RIAU INDONESIA - Enita Deriana Sagala; Eka Purnama Sari; Riska Susanti Pasaribu; Lasria Simamora; Ridesman Ridesman (International Journal of Midwifery Research, 2023)
A common problem is the bad habits of Indonesian mothers when it comes to breastfeeding, namely giving their babies breast milk with white color and thick yellow liquid or colostrum which is thrown away because it is considered a cause of pain. This study used a quantitative descriptive method. The design used in this study was "cross-sectional",  each subject was observed simultaneously at the same time, meaning that the subject was only observed once and was measured according to his condition at the time of observation. The sample in this study were post partum mothers who had newborns who met the criteria for the variables to be analyzed and selected by total sampling with a total sample of 45 people. The results of the Chi Square test by looking at the Pearson Chi-Square obtained a p-Value of 0.001 (<0.05) so it can be concluded that there is a significant relationship between the knowledge of mothers giving birth and giving colostrum to newborns. The results of the Chi Square test by looking at the Pearson Chi-Square obtained a p-Value of 0.001 (<0.05) so it can be concluded that there is a significant relationship between the attitudes of mothers giving birth and giving colostrum to babies born at the Puskesmas Tapung Hilir II District, Kampar Riau Regency. There is a significant relationship between attitude and giving colostrum to newborns at the Puskesmas Tapung Hilir II District, Kampar Regency, Riau, as evidenced by a p-value of 0.001 which is smaller than 0.05.